1996
DOI: 10.1177/0013164496056006008
|View full text |Cite
|
Sign up to set email alerts
|

A Construct Validity Analysis of Scores on Measures of Distributive Justice and Pay Satisfaction

Abstract: Using a multidimensional measure of pay satisfaction (the Pay Satisfaction Questionnaire; PSQ), this study assessed the discriminant validity between scores on a measure of distributive justice and the PSQ using confirmatory factor analysis. Data collected from a diverse sample of employees indicated that the items from both the pay satisfaction scale and the distributive justice scale loaded on the hypothesized dimensions. Various goodness-of-fit measures confirmed the discriminant validity of the two constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The dimension measured retail buyers' satisfaction with a pay raise (four items) (a=.94). Judge (1993) and DeConinck et al (1996) have validated the PSQ. Supervisor satisfaction was measured using four items from a scale developed by Scarpello and Vandenberg (1987) (a=.91).…”
Section: Methodsmentioning
confidence: 99%
“…The dimension measured retail buyers' satisfaction with a pay raise (four items) (a=.94). Judge (1993) and DeConinck et al (1996) have validated the PSQ. Supervisor satisfaction was measured using four items from a scale developed by Scarpello and Vandenberg (1987) (a=.91).…”
Section: Methodsmentioning
confidence: 99%
“…Although most studies using confirmatory analysis found support for the expected four-factor structure (e.g., DeConinck et al, 1996;Judge, 1993;Judge & Welbourne, 1994), not all studies reported consistent results concerning the structure and administration items, leading to questions about what these items are actually measuring. One explanation for some of the inconsistent results obtained is that the factor structure, or number of factors, of the PSQ might depend on contextual characteristics.…”
Section: The Psqmentioning
confidence: 99%
“…States (e.g., DeConinck, Stilwell, & Brock, 1996; R. L. Heneman, Greenberger, & Strasser, 1988;Judge, 1993;Judge & Welbourne, 1994).…”
mentioning
confidence: 99%
“…Organization justice is based on equity theory [1], which demostrated that worker bring his input in the organization like input of education, effort experience etc. and in return of these input he expected the fair outcome of distribution of reward and procedure [11,13], therefore distributed justices is perceive fairness in distribution and allocates of outcomes which base on input provided by employees in organization [6,12,26].…”
Section: Introductionmentioning
confidence: 99%